Age-standardized incidence rates and survival of osteosarcoma in Northern Thailand - Pruksakorn D. (2017)
Osteosarcoma is a common primary malignant bone tumor in children and adolescents. Recent worldwide average incidences of osteosarcoma in people aged 0 to 24 years were 4.3 and 3.4 per million, respectively, with a ratio of 1.4:1. However, data on the incidence of osteosarcoma in Thailand are limited. This study analyzed the incidence of osteosarcoma in the upper northern region of Thailand, with a population of 5.85 million people (8.9% of the total Thai population), using data for the years 1998 to 2012, obtained from the Chiang Mai Cancer Registry (CMCR) at Chiang Mai University Hospital and the Lampang Cancer Registry (LCR) at the Lampang Cancer Hospital, a total of 144 cases. The overall annual incidence of osteosarcoma was 1.67 per million with a male:female ratio of 1.36:1. Incidences by age group (male and female) at 0 to 24, 25 to 59 and over 60 years were 3.5 (3.9 and 3.0), 0.8 (0.9 and 0.6), and 0.7 (0.8 and 0.5), respectively. The peak incidence occurred at 15 to 19 years for males and at 10 to 14 years for females. The median survival time was 18 months with a 5-year survival rate of 43%. Neither the age group nor the 5-year interval period of treatment was significantly correlated with survival during the 15-year period studied.